2021
DOI: 10.3390/pharmaceutics13111803
|View full text |Cite
|
Sign up to set email alerts
|

2D Nanosheets—A New Class of Therapeutic Formulations against Cancer

Abstract: Researchers in cancer nanomedicine are exploring a revolutionary multifaceted carrier for treatment and diagnosis, resulting in the proposal of various drug cargos or “magic bullets” in this past decade. Even though different nano-based complexes are registered for clinical trials, very few products enter the final stages each year because of various issues. This prevents the formulations from entering the market and being accessible to patients. In the search for novel materials, the exploitation of 2D nanosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…Due to the higher specific surface area, nanosheets have more exposure sites, such as degradable sites and catalytic sites. 181 These characteristics make nanosheets perform well in the loading and release of chemotherapeutic drugs, photosensitizers, and immune adjuvants. Therefore, nanosheets have been proved to be an interesting nanoplatform for various cancer diagnoses and treatments.…”
Section: Engineered Nanomaterials With Various Shapes For Dual-mode M...mentioning
confidence: 99%
“…Due to the higher specific surface area, nanosheets have more exposure sites, such as degradable sites and catalytic sites. 181 These characteristics make nanosheets perform well in the loading and release of chemotherapeutic drugs, photosensitizers, and immune adjuvants. Therefore, nanosheets have been proved to be an interesting nanoplatform for various cancer diagnoses and treatments.…”
Section: Engineered Nanomaterials With Various Shapes For Dual-mode M...mentioning
confidence: 99%
“…For medicinal use, the 2D nanocarriers, which are biocompatible and degrade into nontoxic products, are favorable [ 83 ]. These 2D materials possess important properties, such as semiconductivity, high surface area, a chemical nature suitable to be functionalized or decorated, and a stable structure and targeting ability, which can ensure a controlled and sustained release of drugs; these materials can also be used for thermal-based therapies, which predestine them to be applied in cancer therapy [ 84 ]. Recent progress in the surface modification of GR and its derivatives, appropriate for drug delivery systems, was summarized by Jonoush et al [ 85 ].…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…MNPs usually have wide utility in biomedical applications including drug-delivery vehicles in various disease conditions with good biocompatibility, affluent functionality, and controlled release of therapeutic agents [ 192 , 193 ]. In recent years, two-dimensional (2D) materials of metallic origin like nanosheets are also employed as a smart drug-delivery system in different disease conditions [ 194 , 195 ]. It has been reported that MNPs show great advantages not only as anti-aging and anti-acne treatments, and skincare products but also for the management of various skin disorders including psoriasis [ 196 ].…”
Section: Nanoscale Topical Pharmacotherapy In Effective Treatment Of ...mentioning
confidence: 99%